Intervention model by the Social Foundation : Kennedy locality case - Grosso Rincón, Carlos Arturo (Universidad de La Salle. Revistas. Equidad & Desarrollo., 2014)
This paper is presented as a case study, the purpose of which is to understand the intervention processes developed by the Social Foundation (SF) in the Kennedy locality (Bogota) through one of its instruments: direct social projects. Such intervention goes back to 2001, when the company began its approach to this territory, and ends in 2010. In order to speed up the process, the SF defines some guidelines framed in what they call integrated local development model. The paper describes such model, the different phases that were executed for its implementation in the area, how the intervention is perceived from the perspective of some actors and the new intervention logic assumed by the entity in the Bosa and Kennedy localities since 2011, through the interlocal development agenda. A conclusion is drawn about the successful work performed by the entity in the area and how it contributes to strengthening organizational and management processes.